PENTINGNYA KINERJA KEUANGAN DALAM MENGATASI KESULITAN KEUANGAN PERUSAHAAN : SUATU TINJAUAN TEORITIS - Reyner F. Makatita (Universitas Nusa Cendana, 2016)
One of the division which determine sustainability of the company is the division of finance. Theentire activities of the company based on the financial perspective is divided into two main activities,; the activities of companies that use funds (allocation funds) and the activities of companies thatgenerate funds (funds raising). Both activities is called financial function. When the companiesmore excited in allocation funds activities but less in fund raising activities then the companies wereexperiencing financial distress. Continous financial distress will generate of various problems in thecompanies. Therefore, it is expected that the managers have an understanding of good financialperformances. In addition, the managers are expected to have knowledge of financial performancesanalysis techniques in financial problem solving.Keywords : Financial Performances